Improving physical fitness of female students by means of health-saving techniques - Dyachenko, Yulia A. (Физическое воспитание и студенческий спорт)
Relevance of the research lies in the search for optimal methods to improve the components of preparedness against the background of poor health of modern students. The purpose of the study is to analyze the impact of healthsaving practices on the indicators of physical fitness of female students. A group of female students majoring in economics was observed during the period from 2021 to 2024. The students were classified by health status to the main medical group. Classes in physical education were held according to the academic schedule, depending on the stages of training, i.e. from 1 to 2 classes per week. Health-saving tools were used in the form of theoretical, methodological and practical exercises according to the developed comprehensive program using elements of athletics, basketball and fitness during training sessions except for winter and summer holidays. Initially, significantly low results were shown in terms of overall endurance, strength and speed. The values of explosive power, speed endurance and flexibility corresponded to a satisfactory level. At the second stage of the study, diametrically opposite changes in the studied values were recorded: initially low indicators increased against the background of a decrease in others. After correcting the applied program by adding additional exercises in the gym, there was a significant improvement in all indicators. Based on the results obtained, it is concluded that it is advisable to introduce the proposed program into the educational process of physical education in conjunction with traditional methods. The use of health-saving exercises to improve physical fitness has been reliably confirmed.